Well-posedness of the right-hand side identification problem for a parabolic equation - Ashyralyev, A.; Erdogan, A.S. (Український математичний журнал, 2014)
We study the inverse problem of reconstruction of the right-hand side of a parabolic equation with nonlocal conditions. The well-posedness of this problem in Hölder spaces is established. Досліджєно обернену задачу відновлення правої частини параболiчного рівняння з нелокальними умовами. Встановлено коректність цієї задачі у просторах Гьольдера.